Evidence for post-zygotic self-incompatibility in Handroanthus impetiginosus (Bignoniaceae) - Bittencourt Junior, Nelson Sabino [UNESP] (Springer, 2017)
Late-acting self-incompatibility (LSI) has been defined as a genetically controlled self-sterility mechanism that prevents seed set by selfing, despite normal pollen tube growth and ovule penetration in self-pollinated pistils. In species of the Bignoniaceae with LSI, such as Handroanthus impetiginosus, the selfed pistils are characterized by a marked delay in ovule penetration, fertilization, and endosperm initiation, followed by uniform pistil abscission. This highlights the contentious possibility of a post-zygotic self-incompatibility system. However, previous studies were unable to confirm fusion of the sperm and egg cell nuclei in selfed ovules. In the present study, the cytology of the embryo sac, double fertilization, and pistil longevity was investigated in H. impetiginosus using comparative nuclei microspectrofluorometry of DAPI-stained sections of self- vs. unpollinated pistils. Differences in both pistil longevity and ovary size between self- and unpollinated flowers at the time of pistil abscission were significant. Zygotes with double the DNA content in their nuclei relative to unfertilized egg cell nuclei were verified in selfed ovules from the first day after pollination onward, and G1 karyogamy appeared to have occurred. Our cytological analysis clearly indicates that ovules of self-pollinated pistils in H. impetiginosus are fertilized before pistil abscission but no embryogenesis initiation occurs, which strongly supports the idea of a post-zygotic self-incompatibility mechanism.
Keywords: Late-acting self-incompatibility; Self-sterility; DNA microspectrofluorometry; Karyogamy; Fertilization; Female gametophyte; Breeding system